PENGARUH ENVIRONMENTAL AWARENESS, RELIGIOSITY, DAN RISK AVERSION TERHADAP MINAT GEN Z SURABAYA DALAM BERINVESTASI GREEN SUKUK - Affan, Ibnu; Rusgianto, Sulistya (Universitas Negeri Surabaya, 2023)
This study aims to determine the effect of factors such as environmental awareness, religiosity, and risk aversion on the interest of gen Z Surabaya investors in investing green sukuk. The research method uses a quantitative approach with Structural Equation Model (SEM) data analysis. Purposive sampling technique was used to get 90 respondents through a questionnaire. The results of the study state that environmental awareness has no effect on Gen Z Surabaya's interest in investing green sukuk, while religiosity and risk aversion have a significant effect on investment interest. The implications of the results of this research will contribute to attracting more investors, especially Gen Z, to invest in green sukuk.